Effects of Mannitol on Ischemia-Induced Degeneration in Rat Hippocampus - Ryuichi Nakajima; Takeshi Nakamura; Hiroyoshi Miyakawa; Yoshihisa Kudo (Elsevier, 2004)
Although mannitol has been used as an osmotherapeutic drug on brain injury, the clinical efficiency of the drug are still controversial. In the present study, we examined the effects of mannitol on the edema in a hippocampal slice due to brief ischemia. To evaluate the effects, we employed an image analysis system that consists of an infrared-differential interference contrast (IR-DIC) microscope, an infrared CCD camera, and a computer with custom-made software. By this system, severity of the edema can be quantified as the coefficient of variation (CV) of digitalized slice images. The dose-dependent improvement on the deteriorated hippocampal slices could be obtained by administration of mannitol (10, 50, and 100 mM) after 10-min ischemia. However, field excitatory postsynaptic potentials (fEPSP) in CA1 stratum radiatum, which disappeared during 10-min ischemia, were never recovered by mannitol after more than 20-min treatment. fEPSP were blocked by the effective dose of mannitol for morphological recovery, but the effects found to be reversible. Although we failed to find positive rescuing effects of mannitol on the synaptic activities after ischemia, the protective effects of the drug on ischemic edema may rescue the secondary damages around the infarct area. Keywords:: mannitol, ischemia, brain edema, hippocampus, image analysis